The Factor Affecting Customer Satisfaction Towards Internet Service Provider for Millennials in Bandung - Priyambodo, Dyon Andaru; Suharto, Yulianto (Journal of Business and Management, 2020)
Abstract. Service quality has been considered as one of the key elements of service provider success because it can cause customers to be satisfied. This research was conducted at PT. Telekomunikasi Indonesia, Tbk (PT. TELKOM), which is the only state-owned enterprise (SOE) service provider telecommunications and network in Indonesia. Millennials (millennial generation, Generation Y) is the phrase used to generally describe a person who reached adulthood in the early 21st century and covers the generation of people born between 1980 and 2000. Millennials are those who grew up using electronics, the Internet and online social communities. This research aims to determine the level of consumer satisfaction with service quality. This study took 158 respondents, and then performed Servqual calculations to determine the value of GAP, the results of the GAP were used as input data for Importance-Performance Analysis (IPA) which were then identified 4 Attributes that must be considered in the katesius diagram. then the Customer Satisfaction Index (CSI) is calculated, the results of which are very disatisfied.Keywords: Customer Satisfaction, Internet Service Provider, Service Quality, Importance Performance Analysis